Kepemimpinan dan Pendidikan Islam - Puji Khamdani (Madaniyah, 2014)
Leadership is a conscious effort by a person (leader) to be able to realize the goals of the organization through other people by providing motivation so that other people want to carry it out, and for this reason there needs to be a balance between the individual needs of the implementers. A leader of course must understand and understand the basics of leadership to be a leader, both in a small scope, such as family, discussion leaders, and others as well as leaders in a large scope such as organizational leaders, religious leaders, leaders of the country and so on . But there are several factors for the emergence of leadership: first, the situation and condition factors; second, ability factor; third, heredity; fourth, the lifting factor; fifth, the factor of importance. Education is a process of guidance, educating intentionally given to students by adults in order to achieve the goals of education itself. Islamic education is the formation of personality to become human beings who have a morality so that in everyday life they find happiness, peace, and can reflect behavior in accordance with Islamic sharia which is based on the Qur'an, Sunnah Rasul and Ijtihad. Educational leadership is the ability to drive the implementation of education to achieve educational goals. This understanding is in line with the point of view of leadership philosophy which basically upholds the principle of humanity (human relationship).